STUDENTS’ PERCEPTION OF USING BBC ENGLISH LEARNING YOUTUBE CHANNEL IN SPEAKING SKILL - Sholeha, Audia Rahma (Journal of English Teaching and Learning, 2025)
This study examines students' perceptions of the BBC Learning English YouTube channel as a medium to enhance English speaking skills. Using a qualitative descriptive approach, data were collected through questionnaires, and interviews with secondary school students. Results of this study revealed that students had very positive perceptions of using the BBC Learning English YouTube channel as a learning tool to improve their speaking skills. That 85% of students actively used the channel, and 81% reported improved pronunciation and vocabulary. Students found the content engaging, relevant, and easy to understand, though some faced challenges with British accents and speech pace Furthermore, 77% of students feel that they can understand the material they learn from YouTube BBC English Learning well. Overall, the channel proved effective in supporting speaking skill development and enriching the English learning experience when integrated into teaching activities.